12th AIAA/CEAS Aeroacoustics Conference (27th AIAA Aeroacoustics Conference) 2006
DOI: 10.2514/6.2006-2439
|View full text |Cite
|
Sign up to set email alerts
|

Flight Test Results for Uniquely Tailored Propulsion Airframe Aeroacoustic Chevrons: Shockcell Noise

Abstract: Azimuthally varying chevrons (AVC) which have been uniquely tailored to account for the asymmetric propulsion-airframe aeroacoustic interactions have recently shown significant reductions in jet-related community noise at low-speed take-off conditions in scale model tests of coaxial nozzles with high bypass ratio. There were indications that such AVCs may also provide shockcell noise reductions at high cruise speeds. This paper describes the flight test results when one such AVC concept, namely, the T-fan chev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…This represents a very significant change brought to near-field jet noise physics. This peak reduction value is comparable in magnitude to the 5 dB gain mentioned in previous publications on cruise flight tests [21,22,23]. An important difference with results in these papers is the reduction of the high-frequency shock noise by the LINFaN chevrons.…”
Section: Low-noise Fan Nozzles 331 Acoustic Resultssupporting
confidence: 75%
See 3 more Smart Citations
“…This represents a very significant change brought to near-field jet noise physics. This peak reduction value is comparable in magnitude to the 5 dB gain mentioned in previous publications on cruise flight tests [21,22,23]. An important difference with results in these papers is the reduction of the high-frequency shock noise by the LINFaN chevrons.…”
Section: Low-noise Fan Nozzles 331 Acoustic Resultssupporting
confidence: 75%
“…Several fan nozzles are tested on engine 3 in an attempt to reduce shock-associated noise in cruise flight. Mengle et al [21,23] and Bultemeier et al [22] have shown recently that fan chevrons may reduce shock noise in cruise by up to 5 dB in the low frequencies on the external fuselage skin. They have also shown a sensitivity of reduction efficiency on the fan chevron design and the engine operating conditions.…”
Section: Low-noise Fan Nozzles 331 Acoustic Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This paper focuses on the flight tests results of this T-fan chevron nozzle with and without a conventional core chevron nozzle to determine the community noise results at take-off conditions. A companion paper 14 focuses on the acoustics results of these AVC nozzles for shock-cell noise reduction at cruise conditions important for interior cabin noise. In the next two sections we describe flight test configurations and the data analysis method, then we present the flight test results and conclude its applicability to high bypass ratio engines for more stringent noise restrictions.…”
Section: Table 1 Paa Nozzle Flight Test Configurationsmentioning
confidence: 99%